Understanding Service Convenience - Berry, Leonard L.; Seiders, Kathleen; Grewal, Dhruv (Journal of Marketing, 2002)
The subject of service convenience is important in service economies, yet little is known about this topic. The consumer convenience literature—strong in certain respects, underdeveloped in other respects—gives insufficient attention to service convenience. The prevailing pattern is either to treat service convenience generally or to lump services and goods together into an overall convenience construct. The authors seek to stimulate a higher level of research activity and dialogue by proposing a more comprehensive and multidimensional conceptualization of service convenience and a model delineating its antecedents and consequences. The authors build their case by systematically examining the convenience literature, explicating the dimensions and types of service convenience, developing the overall model and related research propositions, and presenting directions for further research.